Analysis of the Influence of AVC Reactive Power Optimization on Line Loss in High Proportion New Energy Area. Issue 1 (1st January 2022) - Liu, SC; Zhang, J; Wang, HB; Wang, XM; Ma, YF; Yan, W
Abstract: In order to effectively reduce line loss, this paper analyzes the impact of AVC reactive power optimization in high proportion new energy areas on line loss under typical mode, and calculates the impact of new energy output on line loss when net load changes, and summarizes the law of AVC reactive power optimization in high proportion new energy areas and the impact of new energy output changes on power grid line loss. The research results show that the line loss rate of the main grid and the line loss rate of each partial voltage tend to decrease in the three modes of new energy generation, small generation and zero generation.